Analisis Upaya Meningkatkan Minat Anggota terhadap Pembiayaan Murabahah dalam Perspektif Manajemen Strategi di Koperasi Jasa Keuangan Syariah (KJKS) Shakira Artha Mulia Purwakarta - Dalingga Yourdita; Deni Lesmana (Jurnal Al-fatih Global Mulia, 2022)
Islamic Financial Institutions (LKS) that operate with a non-usury system do provide distinct benefits for Muslims apart from being muamalah and also seeking the pleasure of Allah SWT. LKS distributes funds to the public in the form of financing. The objectives of this study are: (1) To explain the management strategy used by KJKS Shakira Arha Mula Purwakarta in an effort to increase members' interest in Murabahah financing. (2) To explain what are the driving factors for KJKS Shakira Artha Mulia in implementing the management strategy used. Interest in the community is the main factor that must be owned to attract them to become a member of a group or just to be a user, people will have an interest in an object if they gain an understanding that is easy to accept and also has a realistic element. Here people are often not interested in new things while it can be a help for themselves. This condition can also be divided into non-bank Islamic financial institutions, namely Islamic Cooperatives. The research method in this research research uses qualitative methods. Then the data was analyzed using data analysis methods, data analysis proposed by Miles and Huberman. While checking the validity of the data using observation persistence and data triangulation techniques. Meanwhile, the supporting data is taken from Observations, Documentation, and Statements from Management and Members. The results of the research are: Strategic Management carried out to increase members' interest in financing products: 1) conducting market segmentation, 2) after setting the target market then doing positioning, then 3) carrying out the marketing mix and the strategy implemented is the 4P marketing mix (price, place, product, and promotion). The driving factors in increasing members' interest in murabaha financing products are divided into two classifications. There are internal factors and external factors. Internal Factors Include: Member Participation, and HR Management. The external factors include: Government provisions and policies for cooperatives, cooperative locations, and the KJKS Shakira Artha Mulia Purwakarta service system.